Labour Market Dynamics in South Africa at the Onset of the COVID‐19 Pandemic - Ranchhod, Vimal (S Afr J Econ, 2021)
This paper conducts an analysis of labour market dynamics in South Africa during the initial period of lockdown, from the end of March to the end of April 2020, using the first wave of the NIDS‐CRAM (2020) survey. Within our sample of over 6,000 adults aged 18 to 59, we found that there was a very large decrease in employment. The fraction of the sample that was conventionally classified as employed decreased from 57% in February to 48% in April. If we further exclude temporarily absent workers, which we term “furloughed” employees, this fraction decreases further to 38%. Thus, about one out of every three employed people in our sample either lost their job or did not work and received no wages during April. This has extremely large implications for poverty and welfare. We further analyse the labour market by comparing across demographic groups as defined by race, by gender, by age groups, by geographic areas and by education levels. The over‐arching finding from this analysis is that the job losses were not uniformly distributed amongst the different groups. In particular, groups who have always been more vulnerable – such as women, African/Blacks, youth and less educated groups – have been disproportionately negatively affected.